2017
DOI: 10.1038/s41598-017-01022-w
|View full text |Cite|
|
Sign up to set email alerts
|

Poly-protein G-expressing bacteria enhance the sensitivity of immunoassays

Abstract: The sensitivities of solid-phase immunoassays are limited by the quantity of detection antibodies bound to their antigens on the solid phase. Here, we developed a poly-protein G-expressing bacterium as an antibody-trapping microparticle to enhance the signals of immunoassays by increasing the accumulation of detection antibodies on the given antigen. Eight tandemly repeated fragment crystallisable (Fc) binding domains of protein G were stably expressed on the surface of Escherichia coli BL21 cells (termed BL21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
2
5
0
Order By: Relevance
“…In the present study, we constructed the 8pG on the surface of mammalian cells and demonstrated that the antibody-trapping amount of these 8pG cells was higher than that of 1pG cells. A similar phenomenon was seen in our previous studies; specifically, poly-protein G-expressing bacteria non-covalently conjugated to any detection antibodies and had a higher antibody-trapping amount than mono-protein G-expressing bacteria 40 . The data showed that the polymer protein G (8pG) had higher avidity for trapping antibodies than monomer protein G (1pG).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the present study, we constructed the 8pG on the surface of mammalian cells and demonstrated that the antibody-trapping amount of these 8pG cells was higher than that of 1pG cells. A similar phenomenon was seen in our previous studies; specifically, poly-protein G-expressing bacteria non-covalently conjugated to any detection antibodies and had a higher antibody-trapping amount than mono-protein G-expressing bacteria 40 . The data showed that the polymer protein G (8pG) had higher avidity for trapping antibodies than monomer protein G (1pG).…”
Section: Discussionsupporting
confidence: 88%
“…This process is laborious and time consuming. In this study, therefore, we combined the advantages of cell-based and protein G-based microplates to construct the 8pG cell-based microplate, which can provide extensive surface area and more steric space for trapping capture antibody than a flat-bed well 40 . The 8pG cells, which can be seen as self-renewing microparticles, are easy to obtain and can provide the preferred orientation of a capture antibody by trapping the Fc domain.…”
Section: Discussionmentioning
confidence: 99%
“…No obvious enhancement of absorbance was observed in the wells modified by Anti-IgG k -HRP alone. Therefore, it was confirmed that the PrG increased the sensitivity of the ELISA whereas previous reports have indicated that the presence of the PrG may decrease specificity 70,71 (Fig. 5B).…”
Section: Resultssupporting
confidence: 76%
“…Shieh et al demonstrated that capture ELISA (using a mouse anti-GNNV monoclonal antibody for capture and a rabbit anti-GNNV polyclonal antibody for detection) represents a specific, sensitive tool for GNNV detection [30], but additional costs are incurred for capture antibodies. Furthermore, Hao et al presented a poly-protein G-expressing bacterium (with the AIDA surface expression system) as an antibody-binding microparticle to enhance the sensitivity of immunoassays [51]. Our results reveal that BL21/lpp-Mx-based capture ELISA was more efficient than indirect ELISA at binding GNNV and that it might be a more cost-effective method for GNNV detection in aquaculture.…”
Section: Discussionmentioning
confidence: 69%